MANAJEMEN PROYEK PRODUKSI PUPUK ORGANIK DARI KERANG DARAH - Roby Tan; Febriani Fajar Wati; Mashita Ayuni (Serat Acitya, 2022)
Today, the use of chemical fertilizers is increasing, where more and more people are using chemical fertilizers to accelerate plant growth. In fact, chemical fertilizers have many harmful ingredients that need to be anticipated. Therefore, the production of organic fertilizers from blood clams can be a prospective business opportunity, because in addition to utilizing waste materials that are difficult to decompose, they can be used for the production of useful things, one of which is to support the acceleration of plant growth but with environmentally friendly materials. This study aims to analyze the business development prospects of organic fertilizer from blood clam shells. The research method used is a quantitative method, with data collection techniques through distributing surveys containing questionnaires to respondents who are then processed and further analyzed using descriptive statistical data analysis techniques. The results of the study stated that organic fertilizer from blood clams has positive business prospects because it is beneficial and environmentally friendly.